Functional Analysis of Free Methionine-R-sulfoxide Reductase from Saccharomyces cerevisiae - Le, Dung Tien (American Society for Biochemistry and Molecular Biology, 2009)
Methionine sulfoxide reductases (Msrs) are oxidoreductases that catalyze thiol-dependent reduction of oxidized methionines. MsrA and MsrB are the best known Msrs that repair methionine-S-sulfoxide (Met-S-SO) and methionine-R-sulfoxide (Met-R-SO) residues in proteins, respectively. In addition, an Escherichia coli enzyme specific for free Met-R-SO, designated fRMsr, was recently discovered. In this work, we carried out comparative genomic and experimental analyses to examine occurrence, evolution, and function of fRMsr. This protein is present in single copies and two mutually exclusive subtypes in about half of prokaryotes and unicellular eukaryotes but is missing in higher plants and animals. A Saccharomyces cerevisiae fRMsr homolog was found to reduce free Met-R-SO but not free Met-S-SO or dabsyl-Met-R-SO. fRMsr was responsible for growth of yeast cells on Met-R-SO, and the double fRMsr/MsrA mutant could not grow on a mixture of methionine sulfoxides. However, in the presence of methionine, even the triple fRMsr/MsrA/MsrB mutant was viable. In addition, fRMsr deletion strain showed an increased sensitivity to oxidative stress and a decreased life span, whereas overexpression of fRMsr conferred higher resistance to oxidants. Molecular modeling and cysteine residue targeting by thioredoxin pointed to Cys(101) as catalytic and Cys(125) as resolving residues in yeast fRMsr. These residues as well as a third Cys, resolving Cys(91), clustered in the structure, and each was required for the catalytic activity of the enzyme. The data show that fRMsr is the main enzyme responsible for the reduction of free Met-R-SO in S. cerevisiae.